Superalloys 2016 2016
DOI: 10.1002/9781119075646.ch56
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Carbide Distribution on Ductility of Haynes®282® Forgings

Abstract: Haynes ® 282 ® , a relatively new superalloy is used in gas turbines in form of sheets, plates and forgings. Forgings undergo a series of deformation steps at high temperatures to form complex shapes of components. The deformation on forgings, changes the microstructural features and their distribution, and any change in distribution of microstructural features can affect the mechanical properties of the material. The present study is undertaken to investigate the possible causes of anisotropy in mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…One should also note that larger second phase particles may act to limit grain growth by grain boundary pinning [39], but due to the very sparse distribution of primary carbides in the present alloy this would only be effective much later, in the grain growth stage. At that point, however, it can have a large impact on the spatial grain size distribution, and if there are process related orientation of carbides (stringers) this may also affect the mechanical anisotropy of the final component [20,21].…”
Section: Particle-stimulated Nucleationmentioning
confidence: 99%
See 1 more Smart Citation
“…One should also note that larger second phase particles may act to limit grain growth by grain boundary pinning [39], but due to the very sparse distribution of primary carbides in the present alloy this would only be effective much later, in the grain growth stage. At that point, however, it can have a large impact on the spatial grain size distribution, and if there are process related orientation of carbides (stringers) this may also affect the mechanical anisotropy of the final component [20,21].…”
Section: Particle-stimulated Nucleationmentioning
confidence: 99%
“…Limited efforts have been made towards understanding the effects of prior thermomechanical processing steps, i.e., forging. Joseph et al [20,21] showed that alignment of primary carbides from forging can lead to inhomogeneous grain size distributions and anisotropy in the ductility. Gardner et al [22] applied multistep processing, and showed that SRX during interpass annealing is an important factor, but also that the effects of previous steps on the final microstructure is negligible if the processing conditions during the final step allows sufficient DRX.…”
Section: Introductionmentioning
confidence: 99%
“…The formation from refractory metals, such as Ti, Mo, and W, imparts their high thermal stability, while the NaCl or hexagonal crystal structure is embrittling. During hot deformation, various phenomena around MC carbides including fragmentation, [ 27,124,125 ] nucleation of recrystallized grains, [ 126,127 ] and Zener–Smith pinning [ 45,46 ] have been observed. M 6 C and M 23 C 6 are secondary carbides formed primarily via solid‐state phase transformations during thermo‐mechanical processing.…”
Section: Carbonmentioning
confidence: 99%
“…Preferences for carbide and boride formation, depending on a) C and B, b) Zr and B, and c) C and Zr contents. [ 12,26–28,40,47,48,54,56,57,63–65,80,81,104,106,108,111,137,143,221–224 ] For a more intuitive representation and a table of the used references, readers are referred to the supporting information.…”
Section: Combined Impacts Of Boron Carbon and Zirconiummentioning
confidence: 99%
“…The effect of varying heat treatment parameters on the alloy's mechanical properties have been explored in numerous recent works (e.g. [5][6][7][8][9]). On the other hand, a very low attention has been given so far to the impact of a cold-straining processing [10] on structural and mechanical properties evolution upon the further aging treatment of nickel superalloys.…”
Section: Introductionmentioning
confidence: 99%